2022
DOI: 10.3390/plants11040476
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Phenylpropanoid Derivatives and Alkaloids from the Flowers of Pancratium maritimum L.

Abstract: Regarding our growing interest in identifying biologically active leads from Amaryllidaceous plants, the flowers of Pancratium maritimum L. (Amaryllidaceae) were investigated. Purification of the cytotoxic fractions of the alcoholic extract of the flowers gave a new glycoside, 3-[4-(β-D-glucopyranosyloxy)phenyl]-2-(Z)-propenoic acid methyl ester (1), together with the previously reported compounds 3-methoxy-4-(β-D-glucopyranosyloxy)benzoic acid methyl ester (2), 3-(4-methoxyphenyl)propan-1-ol-1-O-β-D-glucopyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The evaluation of the antiproliferative and growth inhibitory effects of the compounds was carried out using MTT assay, as described before [ 45 , 46 , 47 , 48 ]. Briefly, the cells were incubated overnight in 5% CO 2 /air at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the antiproliferative and growth inhibitory effects of the compounds was carried out using MTT assay, as described before [ 45 , 46 , 47 , 48 ]. Briefly, the cells were incubated overnight in 5% CO 2 /air at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of the antiproliferative and growth inhibitory effects of the compounds was carried out using MTT assay, as described before [45][46][47][48]. Briefly, the cells were incubated overnight in 5% CO 2 /air at 37 • C. The compounds were added at the top row of a 96-well microtiter plate, and descendant serial dilutions (1:4) of the concentration were carried out.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Since then, several other studies have shown the occurrence of many alkaloids belonging to the lycorine-, lycorenine-, montaninetazettine-, galanthamine-, haemanthidine-, crinine-, isocarbostiryl-, narciclasine-, and pancratistatin groups, all biogenetically formed from norbelladines [ 8 ]. Alkaloids with these skeletons have been identified in plants, mainly bulbs, collected in Egypt [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], Bulgaria [ 17 ], Turkey [ 18 , 19 , 20 , 21 , 22 ], Tunisia [ 23 ], Portugal [ 24 ], Spain [ 25 , 26 ], and Italy (Calabria) [ 27 ]. The occurrence of the alkaloids in the bulbs of the different accessions is reported in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from alkaloids, other metabolites have been identified in the bulbs or aerial parts of Pancratium maritimum L. ( P. maritimum) such as chromones, [ 30 , 31 , 32 ], flavonoids [ 30 , 31 , 33 ], phenylpropanoids [ 16 ], phenolic acids [ 33 , 34 ], and alginates [ 23 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the anti-proliferative impact of various species belonging to the Amaryllidaceae family was shown to be promising by a number of studies wherein the percentage of proliferation in cancer cells decreased with respect to time and concentration of plant extract used (Tayoub et al, 2018); (D. T. A. Youssef et al, 2022); (Silva et al, 2008). It is important to mention that the most prominent effect was detected with the highest dose after 48 h, revealing that therapeutic levels of proliferation inhibition are best reached after an incubation of 48 h. Nonetheless, the remaining experiments of this study were performed by incubating SbBEE for 24 h in aims of elucidating its mechanism of action and in order to detect earlier the induced apoptosis at a molecular level.…”
Section: Discussionmentioning
confidence: 99%